Strategi Perbankan Syariah Sebagai Solusi Pengembangan Halal Industry di Indonesia - Rahmayati Rahmayati (Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to improve halal industry through the role of sharia banking with financing channeled by the Islamic banks to finance customers. The method used in this research is qualitative and quantitative research. The qualitative data processing technique is sourced from the analysis of the interviews conducted by the syariah bank and the financing customer, while the quantitative analysis uses secondary time series data derived from publication reports from OJK and BPS from 2005 to 2017 with Eviews software tool. The variables of this research are halal sectors (Halal GDP) as dependent variable; total sharia bank financing; inflation, and export of halal industry as an independent variable. The results of this study proves that sharia banking can encourage the increase and development of halal industrial sector through financing customers in Islamic banks. The econometric results also prove that research variables such as the number of halal industrial sectors will increase with the increase in the business of customers who get halal certification. Despite the inflationary conditions, it does not slow the growth of halal industrial sector.